ANALISIS KINERJA KELEMBAGAAN PEMBANGUNAN PULAU NATUNA - Ambardi, Urbanus M. (Badan Pengkajian dan Penerapan Teknologi, 2007)
Natuna island is specified for an area called Integrated Economic Development Zone. As a pledge area in which the development is being prioritized for escalating regional economic growth, included surrounded area, local, regional, and even national as well. This based on the President Decree number 71 the year of 1996. The changes of government system in the era of “local autonomy” by enacted the Regulation number 22 the year of 1999 concerning Local Government, makes the role of Central Government has been decreasing. Therefore it is required a review regarding current institutional system and the relation between Local and Central Government. In order to get synergetic relationship mentioned above, the concept of future Natuna Island Institution should be formulated